The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1515/cclm-2014-0331
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repeat-testing of common chemistry analytes at critical concentrations

Abstract: The practice of repeating a critical test result appears unnecessary as it yields similar results, delays notification to the treating clinician and increases laboratory running costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 4 publications
1
30
0
Order By: Relevance
“…Survey also revealed that participants do not have an uniform practice regarding consultations with doctors after receiving an information about hemolysed sample. This finding provides additional evidence on harmonization necessity in post-analytical phase ( 12 ), because the issue of automatic resampling might gain specific significance in case of critical values, when a reporting delay may cause adverse outocmes ( 13 ).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Survey also revealed that participants do not have an uniform practice regarding consultations with doctors after receiving an information about hemolysed sample. This finding provides additional evidence on harmonization necessity in post-analytical phase ( 12 ), because the issue of automatic resampling might gain specific significance in case of critical values, when a reporting delay may cause adverse outocmes ( 13 ).…”
Section: Discussionmentioning
confidence: 80%
“…In the future, the same questionnaire could be used in evaluating effectivnes and benefits acheived in educational interventions as recommended in the literature ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…5,6 A growing number of publications have addressed the reporting of critical values. 3,[7][8][9][10][11][12] A CAP-sponsored study of 121 institutions determined that it takes a total of 7 minutes for technician to notify clinicians about a critical result once testing was complete. 13 It took up a lot of time reporting thousands of critical values by laboratories each year.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Deetz et al investigated about 3000 observations for calcium, other assays had 100 observations or less ( 22 , 29 ). Onyenekwu et al found 4.9% outliers out of 91 repeats for calcium at critical concentrations also using CAP/CLIA errors limits ( 21 ). Witte et al aimed to identify outliers in the sense of “errors” defined by a multiple SD e.g.…”
Section: Discussionmentioning
confidence: 99%
“…outliers among routine samples, which may cause erroneous clinical decisions in patient care ( 4 - 15 ). To identify outliers, duplicate measurements may be used ( 16 - 20 ), but are often refrained from, due to economic pressure ( 21 , 22 ). …”
Section: Introductionmentioning
confidence: 99%